Recent tectonic and morphostructural evolution of Byers Peninsula (Antarctica): insight into the development of the South Shetland Islands and Bransfield Basin - Alfaro, P.; López-Martínez, J.; Maestro, A.; Galindo-Zaldívar, J.; Durán-Valsero, J.J.; Cuchí, J.A. (Journal of Iberian Geology, 2010)
Byers Peninsula forms the western extremity of the Livingston Island (Antarctica) in the continental South Shetland Block. This tectonic block is bounded by the South Shetland Trench to the north, the Bransfield back-arc basin to the south, and extends to the South Scotia Ridge on the east. Westwards it is connected to the Antarctic Plate by a broad deformation zone located at the southern end of the Hero Fracture Zone. In Byers Peninsula we analyzed more than 1,200 lineaments, and 359 fault planes from 16 sites, both in sedimentary and intrusive igneous rocks. Statistical analysis of lineaments and mesoscopic fractures, with a length varying between 31 and 1,555 m, shows a NW-SE maximum trend, with two NE-SW and ENE-WSW secondary maximums. Fault orientation analysis shows similar trends suggesting that most of the lineaments correspond to fractures. Due to the absence of striated faults and the lack of kinematic evidence on the regime in most of the analyzed faults we have used the Search Grid paleostress determination method. The results obtained allow us to improve and complete the data on the recent evolution of the South Shetland Block. In this complex geodynamic setting, Byers Peninsula has been subjected to NNW-SSE to NNE-SSW extension related to Bransfield Basin opening and NE-SW and NW-SE local compressions respectively associated to Scotia-Antarctic plate convergence and the South Shetland Trench subduction.